Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3892/mmr.2021.12255
|View full text |Cite
|
Sign up to set email alerts
|

H3K9me2 regulates early transcription factors to promote mesenchymal stem‑cell differentiation into cardiomyocytes

Abstract: Studies have shown that histone H3 at lysine 9 (H3K9me2) is an important epigenetic modifier of embryonic development, cell reprogramming and cell differentiation, but its specific role in cardiomyocyte formation remains to be elucidated. The present study established a model of 5-Azacytidine-induced differentiation of rat bone mesenchymal stem cells (MSCs) into cardiomyocytes and, on this basis, investigated the dimethylation of H3K9me2 and its effect on cardiomyocyte formation by knockdown of H3K9me2 methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…It is well known that H3K9 is widely involved in cell proliferation and differentiation. Our previous study reported that knockdown of the histone methyltransferase G9a increased expression of early transcription factors during the differentiation of MSCs into cardiomyocytes (21). BIX01294 was originally reported to be a G9a inhibitor during a chemical library screen of small molecules and has previously been used in the generation of induced pluripotent stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that H3K9 is widely involved in cell proliferation and differentiation. Our previous study reported that knockdown of the histone methyltransferase G9a increased expression of early transcription factors during the differentiation of MSCs into cardiomyocytes (21). BIX01294 was originally reported to be a G9a inhibitor during a chemical library screen of small molecules and has previously been used in the generation of induced pluripotent stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed the morphology of cells and detected their surface markers, which were consistent with the characteristics of BMSCs. They have been published in relevant articles [ 21 , 22 ]. The BMSCs were then expanded and used for in vitro and in vivo experiments at passages 3–5.…”
Section: Methodsmentioning
confidence: 99%
“…According to the sequence of the CDS region of the gene provided by NCBI, the CDS of NKx2.5, DNMT1, DNMT3A and DNMT3B were synthesised was synthesized and cloned into pcDNA3.1 vector, G9a CDS sequence was synthesised and cloned into pcDNA3.1-Myc vector. The sh-G9a lentiviral interference vector was obtained from a previous study in our laboratory [ 18 ]. The DNMT1-shRNA Plasmid was obtained from Origene (Locus ID 84350).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations